The effects of transport mode use on self-perceived health, mental health, and social contact measures: A cross-sectional and longitudinal study. (November 2018) - Avila-Palencia, Ione; Int Panis, Luc; Dons, Evi; Gaupp-Berghausen, Mailin; Raser, Elisabeth; Götschi, Thomas; Gerike, Regine; Brand, Christian; de Nazelle, Audrey; Orjuela, Juan Pablo; Anaya-Boig, Esther; Stigell, Erik; et al.
Abstract: Background: Transport mode choice has been associated with different health risks and benefits depending on which transport mode is used. We aimed to evaluate the association between different transport modes use and several health and social contact measures. Methods: We based our analyses on the Physical Activity through Sustainable Transport Approaches (PASTA) longitudinal study, conducted over a period of two years in seven European cities. 8802 participants finished the baseline questionnaire, and 3567 answered the final questionnaire. Participants were 18 years of age or older (16 years of age or older in Zurich) and lived, worked and/or studied in one of the case-study cities. Associations between transport mode use and health/social contact measures were estimated using mixed-effects logistic regression models, linear regression models, and logistic regression models according to the data available. All the associations were assessed with single and multiple transport mode models. All models were adjusted for potential confounders. Results: In multiple transport mode models, bicycle use was associated with good self-perceived health [OR (CI 95%) = 1.07 (1.05, 1.08)], all the mental health measures [perceived stress: coef (CI 95%) = −0.016 (−0.028, −0.004); mental health: coef (CI 95%) = 0.11 (0.05, 0.18); vitality: coef (CI 95%) = 0.14 (0.07, 0.22)], and with fewer feelings of loneliness [coef (CI 95%) = −0.03 (−0.05, −0.01)]. Walking was associated with good self-perceived health [OR (CI 95%) = 1.02 (1.00, 1.03)], higher vitality [coef (CI 95%) = 0.14 (0.05, 0.23)], and more frequent contact with friends/family [OR (CI 95%) = 1.03 (1.00, 1.05)]. Car use was associated with fewer feelings of loneliness [coef (CI 95%) = −0.04 (−0.06, −0.02)]. The results for e-bike and public transport use were non-significant, and the results for motorbike use were inconclusive. Conclusions: Similarity of findings across cities suggested that active transport, especially bicycle use, should be encouraged to improve population health and social outcomes. Highlights: Association between transport modes and health was assessed in seven European cities. Bicycle use had the most robust beneficial health effects throughout all the analyses. Positive health effects of walking came up after adjusting for all transport modes. Active transport should be encouraged to improve population health and social outcomes.